We need to talk about Epizelus: 'PTSD' and the ancient world. Issue 1 (19th April 2019) - Rees, Owen
Abstract : In the pursuit to offer validity and lineage to the modern diagnosis of post-traumatic stress disorder (PTSD), non-historical scholars often remove ancient episodes from their social context and retrospectively diagnose them based on our modern diagnostic criteria. This approach reinforces our pre-existing ideas, and form a confirmation bias that does not help to grow our understanding of these injuries. As this article argues, the use of ancient precedents would offer greater benefit to the psychological and medical profession when used to ask new questions rather than reiterate old answers. This article addresses the use of ancient history in the psychological disciplines, especially concerning the topic of post-traumatic stress, and its earlier categorisation as shell shock. Before assessing the non-historical scholarship for the use of ancient precedents, this article sets out the historical debate around the topic and the methodological issues involved in using PTSD as a model with which to examine the ancient world. After which, the use of ancient history by psychological and medical researchers examining PTSD will be assessed. In turn, it will be shown how the removal of historical context has allowed misunderstandings of the original texts and for historical errors to permeate. The story of Epizelus, a man who went blind in battle without incurring any injury, will be used as a case study to show how ancient history has been misused, and vital parts of his life story have been ignored because they do not fit the modern diagnostic model. In particular this article will show how ancient episodes have been used to justify modern ideas and modern understanding, and propose new therapies, without the necessary historical due diligence.